PENGEMBANGAN PROGRAM ELEMEN HINGGA 2-DIMENSI DAN 3-DIMENSI MODEL TANAH NONLINEAR DAN STUDINYA PADA SISTEM PONDASI PILE-RAFT - Widiadi , Rahadian
Abstract : Grouped pile-raft foundation system modeling using 3-D finite element (FE) program is considered to provide a better result compared to simplified 2-D FE program. In this research, a 3-D FE program was developed to model grouped pile-raft foundation system. A 2-D FE program was developed to model single pile-raft foundation system with axisymmetric assumption. Soil and structural element were modeled with isoparametric quadratic triangle element in 2-D analysis. In 3-D analysis, the soil is modeled using isoparametric quadratic brick element (hexahedral) and the pile is modeled with isoparametric quadratic bar element. In 2-D analysis, a quadratic-displacement-isoparametricinterface element model as proposed by Plesha (1989) was used to model friction between the structure and the soil elements. Nonlinear stress-strain soil behavior is modeled using hyperbolic constitutive model. TRIANGLE (Shewchuk, Carnegie Mellon University), a 2-D mesh generation program, and a simple'mesh generation program included in 3-D FE program have made programs easy to be used. Posts processing of the programs were presented using SIGMA/W. The developed programs have been verified and give good results. However, implementation of hyperbolic soil model in 3-D FE program still needs further verifications. A case study of grouped pile-raft foundation system with a certain pile and raft dimension with many numbers of piles and configuration was analyzed using the developed nonlinear 3-D FE program. The 2-D axisymmetric analysis was also performed on single pile-raft under the same dimensions of pile and raft. The analysis shows good results and relation between results of 2-D and 3-D FE analysis was built. Some charts have been generated for practical design purposes although the charts still need to be improved further. The developed programs can be utilized to analyze layered soil. This method is considered to give improvement in analysis of pile-raft foundation system.